(3EOGQI GdJhRjY (B:s (3efXhQ eJcGed (B/s - (3GdUejOYj, eMehO LGSes ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI ddfTQ h GdJhRjY(B, s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B: (3GdJhRjY(B((3Gdeaghe h GdCHYGO(B)(3,bfhGJ GdJhRjY(B((3GdfTCI h GdJWhQ(B)(3, JUeje bfhGJ GdJhRjY,EOGQI bfhGJ GdJhRjY,CfXeI h ESJQGJjLjGJ GdJhRjY,GdhSWGA,GdJhRjY GdeGOj,SdSdI GdJhQjO h fXGe GdEeOGO GdJShjbj,HYV GdCSGdjH GdcejI aj Md eTGcd GdJhRjY(B.s
Keywords: (3GdHjYs; (3GdJShjbs